2017
DOI: 10.1177/0021998316687626
|View full text |Cite
|
Sign up to set email alerts
|

Optimal milling conditions of aeronautical composite material under temperature, forces and vibration parameters

Abstract: Optimal conditions for milling carbon/epoxy composite material were established by response surface methodology. The combination of cutting parameters such as cutting speed (Vc) and chip thickness (h) was set at various design points of a central composite design. Significant regression models describing the changes of vibration level, delamination of composite, cutting force, workpiece temperature were developed with the coefficient of determination greater than 0.90. Results suggested that beyond a threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Response surface methodology (RSM) is a recent optimization technique that can be used to obtain optimal cutting parameters for better cut quality. [33][34][35] Kumar et al 36 examined AWJ cutting of aluminum/ tungsten carbide composite and established a model for lowering surface roughness and increasing MRR using RSM. Ramulu and Arola 37 carried out an AWJ experiment on Gr/Ep laminate to optimize machining parameters using RSM for better machining quality.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface methodology (RSM) is a recent optimization technique that can be used to obtain optimal cutting parameters for better cut quality. [33][34][35] Kumar et al 36 examined AWJ cutting of aluminum/ tungsten carbide composite and established a model for lowering surface roughness and increasing MRR using RSM. Ramulu and Arola 37 carried out an AWJ experiment on Gr/Ep laminate to optimize machining parameters using RSM for better machining quality.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in feed also has a negative effect on cutting forces, causing them to increase [ 17 , 18 ]. Researchers have also shown that an increase in cutting speed, which is beneficial for surface quality, unfortunately also causes damage in the form of delamination and leads to higher processing temperature and cutting forces [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chibane et al. 23 investigated the optimal conditions at which the minimum cutting force, delamination, vibration and temperature were obtained in the milling of composite materials. They observed that delamination damage regularly occurred beyond the threshold vibration and its value increased with an increase in the level of vibration.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that cutting force values decreased with increasing in fiber orientation angle, and cutting temperature value for 45 o fiber orientation angle was less as compared to 135 o fiber orientation angle. Chibane et al 23 investigated the optimal conditions at which the minimum cutting force, delamination, vibration and temperature were obtained in the milling of composite materials. They observed that delamination damage regularly occurred beyond the threshold vibration and its value increased with an increase in the level of vibration.…”
Section: Introductionmentioning
confidence: 99%